Does Cover Crop Radish Supply Nitrogen to Corn?. (1st July 2018) - Ruark, Matthew D.; Chawner, Megan M.; Ballweg, Michael J.; Proost, Richard T.; Arriaga, Francisco J.; Stute, James K.
Abstract : Core Ideas: Radish as a cover crop does not supply nitrogen to the subsequent corn crop. Radish can result in neutral, negative, and positive effects on corn yield. Radish can have substantial nitrogen uptake in the fall, but effects on spring soil nitrogen are variable. Radish ( Raphanus sativus L.) grown as a cover crop can accumulate a significant amount of N when planted by late summer. However, it remains unclear if the N in the radish biomass can supply N to a subsequent corn ( Zea mays L.) crop. The objectives of this project were to: (i) measure radish growth and N uptake, (ii) determine the effect of radish growth on plant available N content in soil throughout the subsequent growing season, and (iii) determine the effects of radish on corn yields and response to N fertilizer. This study was conducted across nine site‐years in northeastern and southern Wisconsin, with radish planted mid‐August following winter wheat ( Triticum aestivum L.) harvest. The experimental design was a randomized complete block, split plot design, with cover crop as the whole plot factor and N rate as the split plot factor. Radish N uptake was ranged from 19.7 to 202 kg ha −1 across all site‐years. The effect of radish on in‐season plant available N (PAN) content differed across growing seasons, with radish both increasing and decreasing PAN. The ANOVA and regression analysis showed mostly neutral effects of radish on corn yield, although corn yield increases and decreases following radish occurred. This research supports the use of radish as a trap crop for fall N, as environmentally meaningful yields of N were contained in plant biomass, but also demonstrates that radish has no N fertilizer replacement value to the subsequent crop.